Flexible, Programmable, Chiroptical Polymer Films of Twisted Stacking Layers for Circular Polarization‐Based Multiplex Color Display. Issue 5 (22nd December 2021) - Xie, Yifan; Yang, Peng; Deng, Linxiao; Feng, Zeyu; Li, Jiahe; Zhang, Chutian; Tang, Xi; Li, Chenyan; Li, Jialei; Xu, Lixin; Zhang, Douguo; Chen, Xin; et al.
Abstract: Flexible films with strong and tunable chiroptical responses are highly desirable and potentially applicable in 3D display, wearable, and implantable devices, etc. Traditional organic or polymer‐based materials typically exhibit weak chiroptical response. Recently, strong chiroptical properties are reported for some chiral inorganic nanostructures and metasurfaces; however, the difficulties to fabricate and control chiroptical properties in a feasible and economical fashion on deformable substrate limit their practical applications. Herein, a simple and cost‐effective method is reported to fabricate flexible chiroptical polymeric films with giant optical activity ( g abs > 0.5) via aligning two anisotropic polydiacetylene (PDA) layers in a twisted fashion. The chromatic transition of PDA is exploited to prepare films with either photonic homostructures or heterostructures to extend spectral range, each featuring distinct frequency dependence and adjustable optical activity. This allows to demonstrate a full color, high brightness, fast responsive, multiplex laser display based on circular polarization. The large chiroptical response of such films, combined with the tunability, flexibility, and compatibility with various substrate choices are also exploited in other applications such as circular polarized luminescence and optical encryption. Abstract : A facile and cost‐effective strategy to fabricate flexible polymeric films of photonic homostructures or heterostructures with giant and tunable chiroptical responses is reported. Such films could be exploited as circular polarization selective color filters. This allows to demonstrate a full color, high brightness, fast responsive laser display, and circularly polarized luminescence‐based optical encryption.